2006
DOI: 10.1007/s00299-005-0065-6
|View full text |Cite
|
Sign up to set email alerts
|

Methyl jasmonate and salicylic acid elicitation induces ginsenosides accumulation, enzymatic and non-enzymatic antioxidant in suspension culture Panax ginseng roots in bioreactors

Abstract: The effects of methyl jasmonate (MJ) and salicylic acid (SA) on changes of the activities of major antioxidant enzymes, superoxide anion accumulation (O2-), ascorbate, total glutathione (TG), malondialdehyde (MDA) content and ginsenoside accumulation were investigated in ginseng roots (Panax ginseng L.) in 4 l (working volume) air lift bioreactors. Single treatment of 200 microM MJ and SA to P. ginseng roots enhanced ginsenoside accumulation compared to the control and harvested 3, 5, 7 and 9 days after treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
110
2
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 201 publications
(119 citation statements)
references
References 43 publications
6
110
2
1
Order By: Relevance
“…Copper ion significantly inhibited Panax ginseng root growth in a bioreactor and resulted in an increase in protein oxidation (21%) which was measured as carbonyl content at concentration of 50 μM. In addition, Cu 2+ stress resulted in increased activities of glucose-6-phosphate dehydrogenase (G6PDH), shikimate dehydrogenase (SKDH), PAL and cinnamyl alcohol dehydrogenase (CAD) [49]. The induced activities of substrate specific peroxidases (caffeic acid peroxidase, chlorogenic acid peroxidase, polyphenol oxidase and β-glucosidase) indicated that these enzymes play an important role in the synthesis of phenolic compounds.…”
Section: Effect Of Different Elicitors and Salts On Callus Biomass Gamentioning
confidence: 99%
“…Copper ion significantly inhibited Panax ginseng root growth in a bioreactor and resulted in an increase in protein oxidation (21%) which was measured as carbonyl content at concentration of 50 μM. In addition, Cu 2+ stress resulted in increased activities of glucose-6-phosphate dehydrogenase (G6PDH), shikimate dehydrogenase (SKDH), PAL and cinnamyl alcohol dehydrogenase (CAD) [49]. The induced activities of substrate specific peroxidases (caffeic acid peroxidase, chlorogenic acid peroxidase, polyphenol oxidase and β-glucosidase) indicated that these enzymes play an important role in the synthesis of phenolic compounds.…”
Section: Effect Of Different Elicitors and Salts On Callus Biomass Gamentioning
confidence: 99%
“…Stock roots of P. ginseng were maintained in Murashighe and Skoog medium (MS, [32]] supplemented with indolebutyric acid (IBA, 5.0 mg L -1 ), kinetin (0.5 mg L -1 ) and sucrose (5%) and cultured as described by Ali et al [13]. These proliferated roots were used as explants and named as Chungbuk National University Line 1 (CBN-1) for further experiments.…”
Section: Stock Root Culturesmentioning
confidence: 99%
“…Exogenous application of methyl jasmonate and/or salicylic acid could induce the expression of many defense genes in different plants [11,12]. Our previous studies have shown that exogenous application of MJ and SA increases ginsenoside content in P. ginseng [13]. Phenolic compounds are ubiquitous in all plant organs and are, therefore, an integral part of the human diet.…”
Section: Introductionmentioning
confidence: 99%
“…그러나 식물체의 생리활성물질은 재 배환경, 수확시기 등에 따라 함량 차이가 크며 신약, 화장품, 건 강식품 소재 등 산업적으로 사용하기 위해서는 연중 생산과 생 리활성물질 변화가 적은 원료를 효율적으로 생산하는 시스템의 확립이 필요하다 (Southwell and Bourke, 2001). (Ali et al, 2006;Savitha et al, 2006). 특히 abiotic elicitor 중, salicylic acid (SA)와 methyl jasmonate (MeJA)는 식물체에서 생리활성물질의 생합성을 유도하는 신호물질로 알려져 있다 (Chen and Chen, 1999;Creelman and Mullet, 1997).…”
Section: 또한 가락지나물의 추출물을 이용하여 여드름 균에 대한 항균unclassified